First-stage LISA data processing and gravitational wave data analysis : ultraprecise inter-satellite laser ranging, clock synchronization and novel gravitational wave data analysis algorithms /: ultraprecise inter-satellite laser ranging, clock synchronization and novel gravitational wave data analysis algorithms. ([2015]) - Wang, Yan
No abstract available